Influence of hydrogenated amorphous carbon underlayer film on the formation of carbon nitride nanostructures / Noor Hamizah binti Khanis - Khanis, Noor Hamizah (2013)

(untitled)
This study is focused on the effects of the structural properties of the hydrogenated amorphous carbon (a-C:H) underlayer on the subsequent formation of carbon nitride nanostructures (ns-CNx). Both layers were prepared sequentially using radio-frequency plasma enhanced chemical vapour deposition (RFPECVD). The a-C:H underlayers and ns-CNx were deposited from pure methane and a mixture of pure methane and nitrogen gases, respectively. The deposition parameters of the ns-CNx were fixed while the parameters relating to the deposition of a-C:H underlayers were varied. Three sets of ns-CNx deposited using fixed deposition parameters on a-C:H underlayer were studied. The first two sets of ns-CNx samples were deposited on a-C:H underlayers grown at different deposition time duration and RF power. The H2 plasma treatment time duration done on a-C:H underlayers were varied for the third set of ns-CNx samples. The structural properties of the a-C:H underlayers studied were characterized using atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy while the structural properties of ns-CNx samples were characterized using field emission scanning electron microscopy (FESEM), FTIR spectroscopy, Raman spectroscopy and Auger electron spectroscopy. It was determined that the a-C:H underlayer with highest surface roughness of 6 nm results in the formation of rigid vertically aligned CNx nanorods. The a-C:H underlayer with highest surface roughness which induced the formation of cone-like structures was shown to have an ordered structure of sp2 clusters and the optimized deposition time duration for the growth of the underlayer was established to be 10 minutes. By varying the applied RF power at 30-80 W, ion bombardment was shown to play an important role in changing the surface morphology of a-C:H underlayer. From the FTIR analysis, the a-C:H underlayer with highest surface roughness shows low CHn band associated with low H content, and dominant sp2 clustering. These properties induced the formation of the said rigid vertically aligned CNx nanorods. It was also found that by tuning the RF power, unique flower-like ns-CNx structure was formed. The treatment of H2 plasma at different time at 3, 5 and 10 minutes on these a-C:H underlayers showed that H bombardment could be used effectively to modify the surface morphology of the underlayer films. In contrast to the high surface roughness requirement for the growth of nanorods, CNx nanotips were formed on smooth a-C:H underlayer film surface. These results showed the effects of changes in structural properties of a-C:H underlayers on the formation of different ns-CNx. The ns-CNx formed were rigid vertically aligned nanorods, nanotip and the rare flower-like structures. Both layers were able to be fabricated in the same system at low deposition temperature of 100 oC without the use of catalyst. High N content and preferential formation of -N≡C bonds are crucial aspects in the formation of rigid and vertically aligned nanorods.